Socio-ecological dimensions of agroforestry called kebun campuran in tropical karst ecosystem of West Java, Indonesia - PARIKESIT PARIKESIT; SUSANTI WITHANINGSIH; FAKHRUR ROZI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Parikesit, Withaningsih S, Rozi F. 2021. Socio-ecological dimensions of agroforestry called kebun campuran in tropical karst ecosystem of West Java, Indonesia. Biodiversitas 22: 122-131.  Traditional and modernized systems combining agricultural and forestry production systems-called agroforestry-was developed by humans under the influence of biophysical and social conditions which often result in heterogeneous landscape. The so-called kebun campuran (mixed gardens) is one of the agroforestry forms that can be encountered in the humid tropics of Indonesia. However, socio-ecological information of this man-made vegetation and its multidimensional functions in particular environmental settings like karst is still limited. This paper aims to elucidate socio-ecological dimensions of kebun campuran in karst ecosystem in Pangandaran District, West Java, Indonesia. A vegetation survey was carried out to reveal the bio-ecological dimensions of kebun campuran complemented with socio-economic questionnaires. The results show that kebun campuran played an important role for the owners as the majority of them gained economic benefits from this agroforest. More than 50% of the owners had their main income from kebun campuran, therefore, kebun campuran was considered a valuable family asset. Kebun campuran ownership put the owner in a higher social status, despite the fact that 80.9% of them had only elementary education background. Correlation analysis showed that there was a very significant correlation between the areas of kebun campuran, rice-field, and homegarden ownership. The analysis also indicated that the economic value of kebun campuran derived from its products increased as its area became larger. There were diverse products like timber, fruits, fuelwood and forages extracted from kebun campuran. Among economically important species were Albizia chinensis (silk tree), Cocos nucifera (coconuts), Manilkara zapota (sapodilla), Musa paradisiaca (banana). Despite its beneficial value, kebun campuran was not intensively managed. On the other hand, the structural vegetation pattern of kebun campuran was the result of various practices carried out by the owners through the processes of introduction, domestication, and selection of plant species. Maintaining kebun campuran in the coastal landscape of Pangandaran might ensure the future of karst ecosystem in this southern coastal area of West Java.